(untitled) (Medico Legal Update, 2021)
Resolving nutritional problems can be done from the time of pregnancy until the child is 5-year-old. The purpose of this study was to determine the relationship between the application of nutrition awareness family program or Keluarga Sadar Gizi (KADARZI) at the household level with the toddler nutrition status. This study was an observational analytic study, with a cross sectional study research design. The sample consisted of 42 toddlers in Libukang Mandiri Village. Data collection was done by weigh and height measurement and nutrition level behavior questionnaire. The results of the research shows that the KADARZI component has a significant relationship. Itwas the consumption of various foods (p value = 0.006), weighing regularly (pvalue = 0.017). Meanwhile, the nutrition level component has no significant relationship, which was iodized salt consumption (p value = 0.681), exclusive breast milk (p value = 0.066), and vitamin A nutrition supplement (pvalue = 0.652). Furthermore, there is a significant relationship of KADARZI on a composite basis with toddler nutrition status(p value = 0.044). The better the application of KADARZI at the household level, the better the nutrition status of toddlers. It is expected that the mother and all family members should behave well in maintaining nutrition level so that the family members always live healthy and have proper nutritional intake.